The Rorschach : - Exner, John E (Wiley, 1993)
New to this edition: All-new case studies describing accurate use of the Rorschach in the assessment of children, adolescents, and adults in a variety of clinical and forensic settings; New research developments; New additions to Exner's Comprehensive System; Expanded reference data, including nonpatient data; Expanded coverage of the cluster approach to organizing data for interpretation